(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
The article highlights the significance of tech and mobile devices for teaching and learning foreign languages. IT tech-based collaborative learning ensures enhanced student involvement, reduced stress, and improved learning. In order to enhance instruction for foreign languages, it is important to consider a variety of options in designing technology. Furthermore, it is crucial to understand different learning issues, theories of language acquisition, methodologies in foreign language teaching, and questions when designing instruction for foreign language learning via computers. The article preface is that innovation can be utilized as a compelling instructing instrument for English dialect learners. The creators talk about an assortment of inquire about outlining how instructors can offer assistance English dialect learners create their dialect abilities through the utilize of innovation.